(untitled) (Third Sector Social Economic Review, 2025)
Understanding the relationship of alexithymia with eating disorders is significant because alexithymia is a risk factor for eating disorders. The importance of the Mediterranean diet has been rising because it provides a sustainable eating model. This study aims to examine alexithymia in the light of eating disorders and adherence to a Mediterranean diet. The study was carried out online in March-June 2022 via social networks. The population of the study consists of 501 adults (72,6% females) aged 18-65. The questionnaires administered to the participants included the REZZY Eating Disorder Scale, Eating Attitude Test (EAT-26), Mediterranean Diet Adherence Scale (MEDAS), and Toronto Alexithymia Scale (TAS-20). Participants at risk for an eating disorder were more likely to have scores in the borderline or clinically significant range with respect to alexithymia compared to participants who were not at risk for an eating disorder. The frequency of alexithymia increased as adherence to a Mediterranean diet decreased and MEDAS scores were higher among individuals who were not alexithymic. It is foreseen that adherence to Mediterranean diet can cause positive effects on psychiatric disorders, and people are suggested to adhere to the Mediterranean diet. Moreover, it is thought that alexithymia and eating disorders might be related to each other.